A comparative study of the occupational aspirations of fourth year vocational and fourth year academic students in selected public high schools of Quezon City - Komkhao, Somsakdi 1942- (s.n.], 1973)
This study was conceived to gain insights into the comparative occupational aspirations of fourth year students both in the vocational as well as in the college preparatory plan of selected high schools of Quezon City under the 2-2 plan. It attempted first to determine the individual and family data of the students, and second, to gain insight into their occupational aspirations as related to acquired data.